2011
DOI: 10.5089/9781463904258.001
|View full text |Cite
|
Sign up to set email alerts
|

Targets, Interest Rates, and Household Saving in Urban China

Abstract: This paper studies a panel of China's provinces over the period 1996-2009 during which urban household saving rates increased from 19 percent of disposable income to 30 percent. It finds that the increase in urban saving rates is negatively associated with the decline in real interest rates over this period. This negative association suggests that Chinese households save with a target level of saving in mind. When the return to saving declines (increases), it becomes more difficult (easier) to meet a target an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…This is not surprising given that the data for financial center countries (e.g., Ireland; Hong Kong, China; Singapore) and heavily indebted countries can be outliers affecting the estimation results. 17 Nabar (2011) and Geerolf and Grjebine (2013) find similar results.…”
Section: Level Impacts Of the Interest Ratesmentioning
confidence: 62%
See 1 more Smart Citation
“…This is not surprising given that the data for financial center countries (e.g., Ireland; Hong Kong, China; Singapore) and heavily indebted countries can be outliers affecting the estimation results. 17 Nabar (2011) and Geerolf and Grjebine (2013) find similar results.…”
Section: Level Impacts Of the Interest Ratesmentioning
confidence: 62%
“…While the interest rate effect on private saving is commonly perceived to be positive, Nabar (2011) notes that the People's Republic of China (PRC) experienced a combination of rising household saving and declining real interest rates during the 2000s. Using province-level data over the 1996-2009 period, Nabar empirically shows that when the return to saving declines, household saving rises.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas studies by Levine et al (2001), Bekaert and Campbell (2003) and Bonfiglioli and Mendicino (2004) show that interest rate has a positive relationship with savings, others such as Nabar (2011) showed that interest rate has a negative relationship with savings particularly in China. Also at the demographic front, the relationship between children and savings is yet to be concluded in both theoretical and empirical strands either at the macro or micro level (Charles, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…Notwithstanding the popular hypothesis that financial repression has contributed to the imbalances by suppressing consumption growth (Lardy, 2008;Nabar, 2011;Pettis, 2013), the speed with which consumption has grown to date suggests that it may be optimistic to hope that even stronger consumption growth in coming years will resolve the imbalances.…”
Section: China's Expenditure Imbalancementioning
confidence: 99%